100-35=n+60

Simple and best practice solution for 100-35=n+60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 100-35=n+60 equation:



100-35=n+60
We move all terms to the left:
100-35-(n+60)=0
We add all the numbers together, and all the variables
-(n+60)+65=0
We get rid of parentheses
-n-60+65=0
We add all the numbers together, and all the variables
-1n+5=0
We move all terms containing n to the left, all other terms to the right
-n=-5
n=-5/-1
n=+5

See similar equations:

| 8=4v-6v | | m-64=-13 | | x-67=11+6 | | 5v-71=3v-35 | | 41.7=b+9.9 | | 2x-1/3-2=x+5/4 | | 6+12x-2x^2=0 | | 03a=6 | | b.30=6 | | U=2u+6 | | 67.5=v-4.56 | | 3k=48k= | | 4.25c=38.25 | | a=5a-8 | | 2(x+50)=18 | | 5p-10=p+18 | | 2y-(y+9)=18 | | 2(3x+3)=3(x-7) | | 10t-9=8t-1 | | (7w+5)(-w-3)=0 | | 8f+8=12 | | 89=5x+6x+1 | | 2(e+7)=-30 | | 4(x-5)+15=3x-6 | | 10=5f+25 | | 6x+2=11x-9= | | -7x-18=-11 | | 11w+70=180 | | 2x–3(–4x+24)=–2 | | 14+9x–9–3x=35 | | 4p-3+3=17+3 | | 7(c-5)=49 |

Equations solver categories